DETERMINANTS OF INTENTION TO DO WHISTLEBLOWING IN BANK PEREKONOMIAN RAKYAT - Ni Putu Ayu Purnama Astuti; I Wayan Suartana; Ni Ketut Rasmini (Transpublika Publisher, 2024)
Whistleblowing is when someone speaks up to expose wrongdoing within an organization, with the goal of protecting it from illegal or unethical behavior. The act of whistleblowing is driven by a deep personal motivation to protect an organization from engaging in illegal activities. This intention can arise due to several factors. This research seeks to analyze on how organizational dedication, individual sacrifices, and ethical thinking impact an individual's decision to report misconduct. This study was conducted at 21 Head Offices of PT Bank Perekonomian Rakyat throughout Denpasar City. A survey was conducted by distributing a questionnaire directly to the participants for collecting data Respondents were selected from employees in the compliance, accounting, teller, credit, and internal auditor divisions, so that the total was 105 respondents. Of the 105 questionnaires distributed, only 92 respondents' answers met the requirements for further analysis using multiple linear regression. The findings of this research reveal that being committed to an organization can increase the likelihood of whistleblowing, while bearing personal costs can also increase the likelihood of whistleblowing. Additionally, moral reasoning does not seem to have an impact on the whistleblowing intention.